2019
DOI: 10.22161/ijeab.45.51
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Yield Components of Several Promising Lines of Red Rice through Application of Mycorrhiza Bio-Fertilizer and Additive Intercropping with Soybean in Aerobic Irrigation System

Abstract: This study aimed to examine the effect of application of a bio-fertilizer containing arbuscular mycorrhizal fungi (AMF) and additive intercropping with soybean relay-planted between double rows of rice on growth and yield components of various promising lines of red rice grown in aerobic irrigation systems on permanent raised-beds. The field experiment, carried out on farmers' riceland in Beleke village of Gerung district in West Lombok, Indonesia, from May to September 2018, was designed according to Split Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
6
0
3
Order By: Relevance
“…Inal et al [6] found that intercropping maize with peanut resulted in higher concentration of nutrients in rhizosphere and in the shoots of both crops. Previous researches using this red rice also reported that grain yield of red rice grown in aerobic irrigation system was higher in intercropping with legume crops than in monocropped or conventional red rice, for example those reported by Dulur et al [8] and Wangiyana et al [11] in intercropping red rice with soybean, and Dulur et al [10] in intercropping red rice with peanut.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Inal et al [6] found that intercropping maize with peanut resulted in higher concentration of nutrients in rhizosphere and in the shoots of both crops. Previous researches using this red rice also reported that grain yield of red rice grown in aerobic irrigation system was higher in intercropping with legume crops than in monocropped or conventional red rice, for example those reported by Dulur et al [8] and Wangiyana et al [11] in intercropping red rice with soybean, and Dulur et al [10] in intercropping red rice with peanut.…”
Section: Resultsmentioning
confidence: 66%
“…From field experiments conducted in other locations, by growing red rice on permanent raised-beds under aerobic irrigation systems, some researchers reported higher grain yields of red rice, i.e. 54.49 g/clump in intercropping with soybean [11], and 2632 filled grains per clump in intercropping with peanut [10]. The low grain yield of the red rice obtained in this research was probably due to prevalent attacks by stink bugs (Leptocoriza acuta) during the seed-filling stage, which resulted in a very high average of percentage of unfilled grain number, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seeds of the red rice lines were pre-germinated first and then direct-dibbled in the base of the previous rice stubbles with the same planting distances as the first year red rice. The entire procedures of growing those red rice lines including types and doses of the fertilizers applied were as explained in Wangiyana et al [10].…”
Section: Implementation Of the Experimentsmentioning
confidence: 99%
“…Chu et al [9] also reported higher number of filled panicles on rice plants grown in a 3 rows: 3 rows rice-peanut intercropping system than on monocropped rice. Intercropping one row of soybean between double-rows of red rice in additive series and mycorrhiza application to the rice and soybean plants not only increased grain yield of various promising lines of red rice [10] but also increased the anthocyanin contents of upland red rice [7].…”
Section: Introductionmentioning
confidence: 99%